The role of public environmental expertise in the provision of the right to subsoil use (Journal of actual problems of jurisprudence, 2019)
In this article the author examines the problems of implementation of public environmental review of RK in grantingthe right to subsoil use and offers some solutions. Examined the role of public ecological expertise in the provision ofmineral rights and the legal regulation of this sector.Key words: ecology, environmental assessment, mineral resources.